(untitled) (Derna Academy Journal for Applied Sciences, 2025)
Work-related musculoskeletal disorders (WRMSDs) are injuries to the musculoskeletal system resulting from occupational activities. Physiotherapists, despite their extensive knowledge of ergonomics and injury prevention, are highly susceptible to WRMSDs during their professional practice. This study aimed to determine the prevalence of WRMSDs among physiotherapists at the Janzour Center for Disability, and to identify associated risk factors and coping strategies. A descriptive study design was employed, utilizing self-administered questionnaires distributed to 27 physiotherapists at the Janzour Center for Disability. Data from 23 completed questionnaires were analyzed using SPSS 26 to identify the most affected anatomical areas, work-related risk factors, and therapist coping strategies. The prevalence of WRMSDs among the study participants was found to be high, with all respondents reporting experiencing WRMSDs. The lower back and neck were the most frequently affected anatomical regions, while the thumb was the least affected. All participants reported experiencing pain, ranging from mild to moderate in severity. The most prevalent work-related risk factors identified were treating a large number of patients and working in awkward positions. Therapists frequently adjusted their own and patients’ positions to mitigate these issues. This study concludes that the prevalence of WRMSDs is high among physiotherapists at the Janzour Center for Disability, primarily due to several identifiable work-related risk factors